Peningkatan Kemampuan Literasi Numerasi Anak Usia 5-6 Tahun Menggunakan Media Loose Part Di Raudhatul Athfal Al Barokah Kecamatan Garut Kota - Aliyah, Siti; Nurajizah, Nina (LP2M STAI Al-Musaddadiyah Garut, 2025)
This research is motivated by the low level of literacy skills of children in Indonesia based on the results of the 2023 PISA test, that there are still 70 percent of Indonesian students who have a literacy level below the minimum standards set. Researchers encountered a similar problem at RA Al Barokah where the level of numeracy literacy skills was still in the low category, namely 25.46%. Researchers are trying to improve the numeracy literacy skills of children aged 5-6 years using loose part media. The aim of this research is to get an idea of ​​the increase in numeracy literacy skills of children aged 5-6 years using loose part media at RA Al Barokah, and to get an idea of ​​the significance of loose part media as a medium to help children understand the concepts of algebra, numbers, geometry , measurement and data analysis. The research method used is a descriptive analysis method with a qualitative approach and uses a Classroom Action Research (CAR) design. The results of this research show that the use of loose part media in improving the numeracy literacy skills of children aged 5-6 years at RA Al Barokah showed a significant impact, seen from the success percentage which reached 100% after the Cycle I, Cycle II and Cycle III actions were given. where each cycle consists of 2 meetings. Keywords : Early Childhood, Numeracy Literacy, Loose Part Media